Pengaruh Financial Distress, Profitabilitas, dan Leverage terhadap Tax Avoidance pada Perusahaan Sektor Consumer Non-Cyclicals Terdaftar di BEI Periode 2019–2023 - Dede Egi Hidayat; Dani Sopian (Jurnal Simki Economic, 2025)
This study aims to examine the effect of financial distress, profitability, and leverage on tax avoidance in consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2019–2023. Tax avoidance is measured by the effective tax rate (ETR), financial distress is measured by the Springate Score, profitability is measured by return on assets (ROA), and leverage is measured by the debt-to-assets ratio (DAR). This study uses a quantitative method. The sample selection was carried out using a purposive sampling technique and obtained 30 companies as samples. Data analysis was carried out using multiple linear regression with the help of the SPSS program. The results of the study indicate that financial distress, profitability, and leverage have no significant effect on tax avoidance. This finding indicates that these variables are not the main factors influencing tax avoidance practices in the consumer non-cyclicals sector.